A Discrete Element Model for Damage and Fatigue Crack Growth of Quasi-Brittle Materials - Xiaofeng Gao; Georg Koval; Cyrille Chazallon (Advances in Materials Science and Engineering)
The repeatedly applied low-intensity loads would lead to the damage and fatigue crack growth of mechanical structures made of quasi-brittle materials. In numerical modelling, these two mechanisms are normally treated differently and separately; the damage is usually associated with nonlocal approaches, while the fatigue crack growth is related to the local stress intensity range at the crack tip. In this study, a discrete element model for damage and fatigue crack growth of quasi-brittle materials is proposed, which is able to model the damage and fatigue crack growth simultaneously in one single model. The proposed model achieves the implementation of a continuum damage model in a discrete element code, which is a helpful enrichment of this numerical method. The evaluation method of the stress intensity range during the damage evolution provides a way to couple both failure mechanisms. This feature allows crack initiation to be induced by localized damage and a progressive transition to a fracture behaviour with the crack propagation. Independent parameters for the fatigue damage model and fatigue crack growth model are admitted without any previous calibration. The numerical results are in good agreement with the theoretical predictions of damage and fracture mechanics, and intact and precracked samples are analysed under fatigue loading to show the consistent coexistence of fractured and damaged zones in a single model.